Investigation on the properties of polypropylene/old corrugated container fibers composites with added foaming agents - Sasan َAbangah (Regional Information Center for Science and Technology (RICeST), 2012)
The influence of reinforcing fibers (old corrugated container fibers called OCC) and addition of foaming agents (Azodicarbinamide and sodium bicarbonate) on density, strength properties and dimensional stability of OCC fiber/polypropylene composite were investigated. Conten of reinforcing fibers constant at 20% and the content of either foaming agent varied as 3, 5 and 7%. Strength properties including MOR, MOE, maximum tensile strength and modulus as well as izod impact strength were measured. Water absorption after 2 and 24 hours soaking in distilled water at 23±2 ºC were measured. Foaming agent decomposition caused some chemical residues in composite and the diffusion and penetration of  polymer  into the fibers structure led to increase in the density from 839.2 kg/m3 for pure polypropylene to 919.2 - 947.9kg/m3 for the composite, MOR and MOE also increased by the addition of foaming agent and the reinforcing fiber. The effect of 5 or 7% sodium bicarbonate was statistically significant and it improved the properties of the composite. Similar results were obtained for tensile strength and the modulus. Reinforcing fibers and foaming agent caused higher impact strength of the composite. Water absorption of the composites was higher than pure polypropylene.